MAXIMIZAREA VALORII DE PIAȚĂ A COMPANIEI – OBIECTIV PRINCIPAL A MANAGEMENTULUI FINANCIAR ÎN GESTIUNEA CAPITALULUI CORPORATIV - Șestacovscaia, Angela (CEP USM, 2018)
The most important goals of financial management in the present is maximizing company’s value.So the causes of increasing importance of this problem are explained as well as the five component of the system of Value Based Management. The author presents some of indicators that can be used for determining company’s market value. The content of the process of Value Based management also is presented in this article.
Keywords: apitalizare; maximizarea bunăstării; valoarea de piață a companiei